The Analysis of Factors Influencing Visiting Decision and Satisfaction at Ekowisata Kampung Blekok Situbondo - Nabilah Rizka Estiningtyas; Tien Lastini; Sofiatin Sofiatin (Dinasti Publisher, 2025)
The decline in visitor numbers at Ekowisata Kampung Blekok implies optimization efforts are needed. The administrator’s ability to understand visitor behaviour can support these efforts, primarily related to visiting decision and satisfaction. These can be achieved by understanding the visitor’s motivation as an internal factor and the destination readiness as an external factor. This research aims to analyze the factors influencing visiting decision and the visitor’s satisfaction. The questionnaire with five-point likert sclae was distributed to 165 visitors using a purposive sampling. Data was analyzed with structural equation modelling – partial least square using SmartPLS 3.0 application. The result shows that the visiting decision is directly influenced by service quality (consist of tangible, responsiveness, reliability, assurance, eco-activities, empathy, eco-learning, and eco-practices) and marketing mix (consist of product, promotion, price, physical evidence, place, and process). Besides, visitor satisfaction is affected directly by service quality and visiting decision.